Essential oil phytochemistry and antifungal activity of lemongrass inoculated with arbuscular mycorrhizal fungi under different phosphorous levels - Lermen, Caroline; da Cruz, Rayane Monique Sete [UNESP]; Gonçalves, Carlos Henrique de Souza; Pinc, Mariana Moraes; Otênio, Joice Karina; da Silva, Camila; Alberton, Odair (Elsevier, 2024)
This study aimed to investigate the effect of inoculating Cymbopogon citratus (lemongrass) with arbuscular mycorrhizal fungi (AMF) Rhizophagus clarus and Claroideoglomus etunicatum under low and high phosphorus (P) levels on essential oil (EO) content, composition, and minimum inhibitory concentration (MIC) for four isolates of phytopathogenic fungi of the genus Fusarium. The EO content was obtained by the hydrodistillation process, followed by the evaluation of chemical constituents using gas chromatography coupled to mass spectrometry and MIC by microdilution in broth. The EO content increased 2.5-fold due to high P and inoculation with C. etunicatum compared with uninoculated under low P. Twenty-two compounds were identified in EO. The major components were citronellol, geraniol, citral, neral and geranial. The EO of lemongrass showed a MIC in the four phytopathogenic fungal isolates. Therefore, the secondary metabolites were influenced by P levels and AMF inoculation, increasing EO's content (until 2.5-fold), chemical composition (citral, neral and geranial) and MIC.
Keywords: Antimycotic; Essence; Lemongrass; Mycorrhiza; Rhizosphere